Trends in mortality and hospital admission rates for abdominal aortic aneurysm in England and Wales, 1979-1999. - Filipovic, M; Goldacre, M; Roberts, SE; Yeates, D; Duncan, M; Cook-Mozaffari, P (2005)
BACKGROUND: The aim of this study was to investigate trends in population-based mortality, hospital admission and case fatality rates for abdominal aortic aneurysm (AAA) from 1979 to 1999. METHODS: This was an analysis of routine statistics from 79 495 death certificates in England and Wales and 3217 hospital inpatient admissions in the Oxford Region. RESULTS: Mortality rates for all AAAs increased between 1979 and 1999 from 13 to 25 per million in women and from 80 to 115 per million in men. Admission rates increased in the same time interval from three to 22 admissions per million per year in women, and from 52 to 149 per million per year in men. Case fatality rates for all non-ruptured AAAs that were operated on decreased from 25.8 to 9.0 per cent and for all ruptured AAAs from 69.9 to 54.4 per cent. CONCLUSION: Mortality rates and hospital admission rates for AAA rose in men and even more so in women between 1979 and 1999. Perioperative mortality for ruptured AAA declined a little during the study but nonetheless was still very high at the end. This reinforces the importance of detecting and treating AAA before rupture occurs.